Ptosis as the only manifestation of diabetic superior division oculomotor nerve palsy: A case report. Issue 46 (November 2017) - Chou, Ping-Yin; Wu, Kun-Han; Huang, Poyin
Abstract: Rationale: Diabetic oculomotor nerve palsies, also called ischemic third nerve palsies, are the most common etiologic subset of oculomotor nerve palsy in adults. Diabetic oculomotor nerve palsies typically present with ptosis and diplopia, but pupillary function is often spared. The oculomotor nerve separates into superior division and inferior division, with the superior division innervating the superior rectus and levator palpebrae superioris. The diabetic oculomotor nerve palsy may affect isolated superior or inferior division of the oculomotor nerve, but diplopia usually exists. Patient concerns: A 56-year-old female was admitted to our hospital for acute onset right upper lid ptosis. The patient denied diplopia or other new focal neurologic symptoms. The neurological examination revealed ptosis of the right upper eyelid only, and other neurological examination revealed negative findings. Diagnoses: The diagnosis of diabetes-associated oculomotor nerve palsy was made, with acute ptosis as its only manifestation. Interventions: We controlled her blood sugar aggressively with insulin. Outcomes: After the hyperglycemia improved, the right side ptosis recovered partially within one week. Lessons: From this case, we suggest that when evaluating patients with acute onset ptosis as the only manifestation, diabetic-vasculopathic neuropathy should be considered. This case also implies that the most interior portion of the third cranial nerve may consist of nerve fibers mainly innervating the levator palpebrae superioris.